Stem cell therapy for central nerve system injuries: glial cells hold the key - Xiao, Li (Medknow Publications & Media Pvt Ltd, 2014)
Mammalian adult central nerve system (CNS) injuries are devastating because of the intrinsic difficulties for effective neuronal regeneration. The greatest problem to be overcome for CNS recovery is the poor regeneration of neurons and myelin-forming cells, oligodendrocytes. Endogenous neural progenitors and transplanted exogenous neuronal stem cells can be the source for neuronal regeneration. However, because of the harsh local microenvironment, they usually have very low efficacy for functional neural regeneration which cannot compensate for the loss of neurons and oligodendrocytes. Glial cells (including astrocytes, microglia, oligodendrocytes and NG2 glia) are the majority of cells in CNS that provide support and protection for neurons. Inside the local microenvironment, glial cells largely influence local and transplanted neural stem cells survival and fates. This review critically analyzes current finding of the roles of glial cells in CNS regeneration, and highlights strategies for regulating glial cells’ behavior to create a permissive microenvironment for neuronal stem cells.